Leaflet thrombosis in transcatheter aortic valve intervention: mechanisms, prevention, and treatment options - Koren, Ofir; Patel, Vivek; Chakravarty, Tarun; Jilaihawi, Hasan; Gupta, Aakriti; Sadri, Shirin; Makkar, Raj R. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Transcatheter aortic valve intervention (TAVR) has emerged as a promising alternative to surgical aortic valve replacement for patients with severe aortic stenosis. However, leaflet thrombosis has raised concerns about the long-term durability and outcomes of TAVR. This study aims to provide an overview of the mechanisms, prevention strategies, and treatment options for leaflet thrombosis in TAVR. Clinical evidence Leaflet thrombosis refers to the formation of blood clots on bioprosthetic valve leaflets, leading to impaired leaflet mobility, early valve degeneration and dysfunction, and potential clinical implications. While the mechanisms underlying thrombus formation on valve leaflets are not fully understood, several factors, such as altered blood flow patterns within valve neosinuses, prothrombotic surfaces, and patient-related causes, have been implicated. Two distinct entities have been identified, namely, hypoattenuated leaflet thickening and restricted leaflet motion. Their occurrence appears dynamic over time and is related to the valve type. Imaging, including transesophageal echocardiography and multidetector computed tomography, plays a crucial role in the diagnosis and follow-up of leaflet thrombosis. Prevention and treatment options Preventing leaflet thrombosis requires a comprehensive and tailored approach involving identifying high-risk patients, close monitoring, and antithrombotic therapy. Antithrombotic therapy with dual antiplatelet agents or anticoagulation is commonly employed in TAVR patients, although the optimal regimen is yet to be defined. Novel antithrombotic agents, such as direct oral anticoagulants, are being investigated for their efficacy and safety in preventing leaflet thrombosis. When leaflet thrombosis is detected, treatment options include intensified antithrombotic therapy, valve-in-valve intervention, or balloon valvuloplasty. The long-term outcomes and impact of leaflet thrombosis on valve durability and patient prognosis are areas of ongoing research. Summary Leaflet thrombosis in TAVR is a considerable complication affecting valve function and patient outcomes. Understanding the mechanisms underlying thrombus formation and implementing appropriate prevention strategies are essential for mitigating this risk. Treatment options aim to restore leaflet mobility and optimize valve performance. Further research is needed to establish standardized protocols for antithrombotic therapy, identify high-risk patient populations, and determine the long-term consequences of leaflet thrombosis on TAVR outcomes.